Molecular Docking Studies of Methamphetamine and Amphetamine-Related Derivatives as an Inhibitor against Dopamine Receptor - Foroughi, Kobra; Khaksari, Mehdi; Shayannia, Asghar (Current Computer - Aided Drug Design, 2020)
Background: The catecholamines such as dopamine, norepinephrine, and epinephrine are neurotransmitters that regulate different physiological functions of the central nervous system. Some evidence suggests that the degeneration of dopamine neurons in the substantia nigra contributes to Parkinson’s Disease (PD), which is a neurodegenerative disorder and it is responsible for the major symptoms of PD. It is suggested that replenishment of striatal dopamine through the oral administration of the dopamine precursor, levodopa, can compensate for the lack of endogenously produced dopamine. Some studies have shown competitive inhibition of dopamine receptor such as methamphetamine, and other amphetamine-related derivatives, which block dopamine receptor activity to uptake dopamine. Methods: In this study, 3D structures of amphetamine, methamphetamine, cocaine, methylphenidate, cathinone, MDMA, and mephedrone were obtained from the PubChem database, which has reported some evidence about their inhibitory effect with dopamine receptor. Then, these structures were provided for molecular docking analysis by Autodock Vina software. Eventually, the binding energies between docked dopamine receptor and them were calculated and their interactions were prognosticated. Results: Our results indicated that all chemicals can interact with dopamine receptor molecule in the active site of dopamine and the minimum binding energies belong to Cocaine and Methylphenidate with -7.9 Kcal/mol and -7.2 Kcal/mol, respectively. Conclusion: It might be concluded that amphetamine, methamphetamine, cocaine, methylphenidate, cathinone, MDMA, and mephedrone could act as potential inhibitors of DA receptor for dopamine uptake, which could cause degenerative disorders.
Keywords: Autodock Vina